Kandungan Logam Berat Merkuri (Hg) pada Ikan Cencen (Mystacoleucus marginatus) di Sungai Batang Gadis Kabupaten Mandailing Natal Heavy Metal Content of Mercury (Hg) in Cencen Fish (Mystacoleucus marginatus) in Batang Gadis River Mandailing Natal Regency - Latifa Sari Dalimunthe; Mohammad Basyuni; Ani Suryanti (AQUACOASTMARINE, 2015)
Mercury (Hg) is a dangerous pollutant because its toxic when accumulating in the tissues of organism and difficult to degraded in environment. Mercury can pollute the environment of river water that comes from galundung waste to waters area without management or handling. The objective of this research Are to analyse the heavy metals concentrations Hg and in water and soft tissue of cencen fish, analyse the effect of mercury on cencen fish gill histological observations. This study was conducted in Batang Gadis River Mandailing Natal Regency from June until August 2014. Sampling method is purposive sampling, which located 3 station. Water and fish sampling was taken for 2 weeks. The result of this research has showed that average out heavy metals Hg concentrations in the water are between 0,00015 − 0,00043 ppm, and in tissue of fish between 0,00128 − 0,01097 ppm. Concentrations of Hg in the river water and tissue was below of the quality standard. The result of the calculation of low value fish bioaccumulation factor are between 12,88 – 25,51. This study showed that cencen fish in Batang Gadis River accumulated Hg. The observation of the gill histology in all stations showed availability of edema, hyperplasia, fusion of lamellae and mineralization.Keywords: Batang Gadis River, Mercury (Hg), Accumulation, Histology